Complete chloroplast genome of the rare medicinal vegetable Allium hookeri. Issue 1 (2nd January 2022) - Ren, Fengming; Wang, Liqiang; Zhuo, Wei; Chen, Dongliang; Huang, Hongyan; Zhang, Lansheng
Abstract: Allium hookeri is a rare medicinal plant with unique flavor. In this study, the first complete chloroplast (cp) genome of A. hookeri was sequenced and assembled based on the next generation sequencing. The cp genome is 153, 592 bp in length, including a large single-copy (LSC) region of 82, 609 bp, a small single-copy (SSC) region of 17, 487 bp, and a pair of inverted repeat (IR) regions of 26, 748 bp each. The genome encodes 131 genes, including 86 protein-coding genes, 39 tRNA genes, and six rRNA genes. The GC content of whole genome is 36.99%. The phylogenetic analysis based on 24 complete cp sequences revealed that A. hookeri was at the base of the phylogenetic tree, indicating an older species in the Allium genus.